PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH BERBASIS PREZI UNTUK MENINGKATKAN HASIL BELAJAR MENGGUNAKAN MODEL ASSURE - Alvina Siti Asiyah; Sumardi Sumardi; Nurul Umamah (Jurnal Pendidikan Sejarah Indonesia, 2022)
Learning in the 21st century requires students to have skills, knowledge and abilities in the fields of technology, media and information. This research is a development research that aims to see the magnitude of the increase in student learning outcomes who are taught using Prezi-based learning media with the ASSURE model. This development research has produced a product in the form of Prezi-based learning media that has been validated by experts and users. Learning resources are designed according to student characteristics and based on user needs analysis. The results of content validation in the field of study for Prezi media are 96 percent, in the very appropriate category, 98 percent in learning design experts in the very appropriate category, linguists 94 percent in the very appropriate category. Educator user test of 80 percent product is very feasible. The average small group learning outcomes for the pre-test was 48.50, while the post-test was 83.50. In the field test, the average learning outcomes for the pre-test were 47.14 while the post-test was 85.71. So it can be concluded that there was an increase in learning outcomes in the small group by 72.2 percent with high qualifications and in the field trial an increase in learning outcomes by 82 percent with very high qualifications. The conclusion from the research and development of Prezi-based learning media is feasible to use and proven to improve student learning outcomes. Recommendations made based on the results of this study are the use of technology-based media so as to improve student learning outcomes. Pembelajaran di abad 21 menuntut siswa untuk memiliki keterampilan, pengetahuan dan kemampuan di bidang teknologi, media dan informasi. Penelitian ini merupakan penelitian pengembangan yang bertujuan untuk melihat besarnya peningkatan hasil belajar siswa yang diajar menggunakan media pembelajaran berbasis Prezi dengan model ASSURE. Penelitian pengembangan ini telah menghasilkan produk berupa media pembelajaran berbasis Prezi yang telah divalidasi oleh ahli dan pengguna. Sumber belajar dirancang sesuai dengan karakteristik siswa dan berdasarkan analisis kebutuhan pengguna. Hasil validasi isi bidang kajian untuk media Prezi adalah 96 persen, pada kategori sangat sesuai, ahli desain pembelajaran 98 persen pada kategori sangat sesuai, ahli bahasa 94 persen pada kategori sangat sesuai. Uji pengguna pendidik produk 80 persen sangat layak. Rata-rata hasil belajar kelompok kecil untuk pre-test adalah 48,50, sedangkan post-test adalah 83,50. Pada uji lapangan rata-rata hasil belajar pre-test 47,14 sedangkan post-test 85,71. Sehingga dapat disimpulkan terjadi peningkatan hasil belajar pada kelompok kecil sebesar 72,2 persen dengan kualifikasi tinggi dan pada uji coba lapangan terjadi peningkatan hasil belajar sebesar 82 persen dengan kualifikasi sangat tinggi. Kesimpulan dari penelitian dan pengembangan media pembelajaran berbasis Prezi layak digunakan dan terbukti dapat meningkatkan hasil belajar siswa. Rekomendasi yang dibuat berdasarkan hasil penelitian ini adalah penggunaan media berbasis teknologi sehingga dapat meningkatkan hasil belajar siswa.